Karin Lednicka and the Czech literary traumatology - Heller, M. Jan (Bohemica Olomucensia, 2025)
The study attempts to place Karin Lednicka's trilogy Sikmy kostel (The Leaning Church) within the framework of literary traumatology. This concept is understood as a flexible set of approaches that take into account memory, displacement, and collective experiences of suffering. Rather than focusing on primary textual analysis, the study draws from the novels' reception, which allows for an examination of their social effects. A key element is the vanished landscape of the town of Karvina, which functions as a medium of traumatic memory and a site of symbolic significance. The fictional narrative transforms memory traces into narratives that help shape collective identity. The ruined space also serves as a critique of modernity, industrialization, and the ideology of progress. The author of the trilogy employs strong strategies of authentication, some of which have been criticized as problematic. The reception reveals a tension between aesthetic evaluation and the therapeutic effect of the work on the reading community. The study also discusses the ambivalent role of nostalgia as a possible defense mechanism in the face of trauma. It concludes that even traditionally written literature can play an important role in the collective processing of historical wounds.
Keywords: literary traumatology; cultural memory; collective identity; representation of facial memory in space; authenticity; trauma a fiction